Pengembangan Bahan Ajar Pendidikan Agama Islam Berbentuk Mailing List - Marzuki, Said (Pascasarjana IAIN Lhokseumawe, 2024)
This study aims to conceptually examine the development of Islamic Religious Education (IRE) instructional materials using mailing lists as an innovative learning strategy in the digital era. Employing a qualitative approach with content analysis, the research explores primary and secondary literature related to instructional material development, digital media, and IRE pedagogy. The analysis was conducted through descriptive, textual, and reflective methods to interpret the meaning, structure, and relevance of mailing list–based instructional content. The findings indicate that mailing lists hold significant potential as an alternative learning medium that facilitates material distribution, religious discourse, and character formation among students. The development of instructional materials via mailing lists can follow the Four-D model (Define, Design, Develop, Disseminate), which is adaptable to technological advancements and learner needs. Mailing lists also support digital literacy, independent learning, and active participation in IRE instruction. Thus, the development of IRE instructional materials through mailing lists represents an innovative strategy that not only addresses pedagogical challenges in the digital age but also strengthens students’ spiritual values and character holistically.